Comparison of postoperative lymphocytes and interleukins between laparoscopy-assisted and open radical gastrectomy for early gastric cancer. Issue 1 (January 2019) - Xia, Xiang; Zhang, Zizhen; Xu, Jia; Zhao, Gang; Yu, Fengrong
Objective: This study aimed to study the effects of laparoscopic-assisted radical gastrectomy (LAG) and open radical gastrectomy (OG) on immune function and inflammatory factors in patients with early gastric cancer. Methods: Seventy-five patients with pT1N0M0 gastric cancer in Ren Ji Hospital from August 2017 to January 2018 were studied. Lymphocytes subsets and interleukins were compared preoperatively and on the third postoperative day (POD3) and seventh postoperative day (POD7). Results: There were no significant differences in age, sex, body mass index, duration of the operation, estimated blood loss, total gastrectomy rate, postoperative first fluid diet, and the levels of preoperative lymphocytes subsets and interleukins between the two groups. The number of CD4+ T cells and the CD4+/CD8+ ratio in the LAG group were significantly higher than those in the OG group on POD3. However, the number of CD8+ T cells, and interleukin-6 and interleukin-8 levels in the LAG group were significantly lower than those in the OG group on POD3. Conclusions: Laparoscopy can effectively reduce the levels of inflammatory factors and has less effect on the immune system than OG.